Сравнительная иммуногистохимическая характеристика экспрессии рецепторов эстрогена-α и прогестерона, р16 и р53, Ki-67 и каспазы-3 в инвазивной эндометриоидной аденокарциноме тела матки различной степени дифференцировки - Туманский, В. А.; Чепец, А. В.; Туманський, Валерій Олексійович; Чепець, Олександр Вікторович; Tumanskiy, V. A.; Chepets, A. V. (My University, 2016)
При помощи иммуногистохимических и морфометрических методик изучена инвазивная рТ1-4NxMxG1-3 эндометриоидная аденокарцинома (ЭА) различной дифференцировки в удаленной матке 56 больных. Установлено, что по мере ухудшения дифференцировки ЭА в ее клетках снижается уровень экспрессии рецепторов эстрогена-α (РЭ-α), рецепторов прогестерона (РП), каспазы-3 и возрастает уровень экспрессии р16, Ki-67, а в клетках опухолевой стромы увеличивается уровень экспрессии каспазы-3. Степень дифференцировки опухоли имеет достоверные связи с уровнями экспрессии РЭ-α (γ=-0,68), РП (γ=-0,78), р53 (γ=-0,45 в ЭА низкой и высокой экспрессией р53; γ=0,75 в ЭА с гиперэкспрессией р53), р16 (γ=0,76), Ki-67 (γ=0,34), каспазы-3 (γ=-0,84) в клетках ЭА и с уровнем РЭ-α (γ=-0,36), каспазы-3 (γ=0,84) в клетках опухолевой стромы. З метою імуногістохімічної характеристики експресії рецепторів естрогену-α і прогестерону, р16, р53, Ki-67, каспази-3 клітинами інвазивної ендометріоїдної аденокарциноми ендометрію різного диференціювання Імуногістохімічними та морфометричними методиками досліджена інвазивна рТ1- 4NxMxG1-3 ендометріоїдна аденокарцинома (ЕА) в видаленій матці 56 хворих. Встановлено, що з погіршенням диференціювання ЕА в її клітинах знижується рівень експресії рецепторів естрогену-α (РЕ-α), рецепторів прогестерону (РП), каспази-3, зростає рівень експресії р16, Ki-67, а в клітинах пухлинної строми збільшується рівень експресії каспази-3. Ступінь диференціювання пухлини має достовірні зв'язки з рівнями експресії РЕ-α (γ=-0,68), РП (γ=-0,78), р53 (γ=-0,45 в ЕА з низькою та високою експресією р53; γ=0,75 в ЕА з гіперекспресією р53), р16 (γ=0,76), Ki-67 (γ=0,34), каспази-3 (γ=-0,84) в клітинах ЕА та з рівнем експресії РЕ-α (γ=-0,36), каспази-3 (γ=0,84) в в клітинах пухлинної строми. Endometrial cancer occupies the sixth place among newly diagnosed neoplasm in women each year. Objective. Immunohistochemical characterization of the expression of the estrogen receptors-α, progesterone receptors, p16, p53, Ki-67, caspase-3 by the cells of invasive endometrioid endometrial adenocarcinomas of various grade. Methods. The invasive endometrioid endometrial adenocarcinoma (stage pT1-4MxNxG1-3) in the uteruses of 56 perimenopausal women with the verified diagnosis of endometrial cancer were analyzed. For this purpose, immunohistochemical and morphometrical studies were used. Results. The expression levels of p16 and Ki-67 significantly reduce in the tumor cells (р<0,05). The caspase-3 expression level significantly increased in the tumor stromal cells with FIGO (International Federation of Gynecology and Obstetrics) grade increasing (p<0.05). The FIGO grade of the invasive endometrioid endometrial carcinoma has significant relations with the expression levels of the estrogen receptor-α (γ=-0,68), progesterone receptors (γ=-0,78), p53 (γ=-0,45 in the group of adenocarcinomas with low and high expression levels of p53; γ=0,75 in the adenocarcinomas group with overexpression of p53 ), p16 (γ=0,76), Ki-67 (γ=0,34), caspase-3 (γ=-0,84) in the tumor cells and estrogen receptor -α (γ = -0,36), caspase-3 expression levels in tumor stromal cells (γ = 0,84). Conclusion. With increasing of FIGO grade of the invasive endometrioid endometrial adenocarcinoma the sensitivity of tumor cells to regulatory signals of estrogen and progesterone decreases. The expression level of p16 increases, which indicates the violations of p16-associated cell cycle control mechanism. The proliferation level of tumor cell increases and the level of tumor cells apoptosis decreases. Key words: endometrial neoplasms, estrogen receptors, progesterone receptors, tumor suppressor protein p53, cyclindependent kinase inhibitor p16, ki-67 antigen, caspase 3, neoplasm grading.
Порівняльна імуногістохімічна характеристика експресії рецепторів естрогену-α, та прогестерону, р16 і р53, Ki-67 і каспази 3 в інвазивній ендометріоїдній аденокарциномі тіла матки різного ступеню диференціювання
Comparison of immunohistochemical characteristics of expression estrogen receptorsalpha, progesterone receptors, p16, p53, Ki-67 and caspase 3 in invasive endometrial adenocarcinoma of different grade
Keywords: карцинома эндометрия; рецепторы эстрогена – α; рецепторы прогестерона; р53; р16; Ki-67; каспаза3; степень опухолевой дифференцировки; карцинома ендометрію; рецептори естрогену – α; рецептори прогестерону; р53; р16; Ki-67; каспаза 3; ступінь пухлинного диференціювання; endometrial neoplasms; estrogen receptors; progesterone receptors; tumor suppressor protein p53; cyclindependent; kinase inhibitor p16; ki-67 antigen; caspase 3; neoplasm grading